Bioactivities related to pigments content of Sargassum sp. Collected from Jeddah coast, Saudi Arabia, Red Sea - Bandar A. Al-Mur; Waleed A. Alsiary (Egyptian Journal of Aquatic Research)
The study highlights the diverse bioactive potential of the brown alga Sargassum sp., collected from the Jeddah coast in Saudi Arabia. The acetone extract of Sargassum sp was comprehensively analyzed for its pigment composition and biological activities. Thirteen individual pigments were identified by using HPLC, Chlorophyll-a (12.3 μg/g), Chlorophyll-d (3.5 μg/g), α-Carotene (14.1 μg/g), β-Carotene (11.8 μg/g), xanthophylls-fucoxanthin (11.29 μg/g), phycobiliproteins that included phycourobilin, phycocyanobilin, phycourobilin, phycoerthrobilin, phycoerythrin phycoerythrocyanin, phycocyanin, allophycocyanin with a total amount of 62.6 μg/g. The IC50 for antioxidant activity was 19.65 µg/mL for Sargassum sp. extract, compared to the IC50 of L-ascorbic acid (2.82 µg/mL), indicating moderate antioxidant potential. The extract’s anti-inflammatory activity showed an IC50 of 4.13 µg/mL, demonstrating stronger anti-inflammatory activity than the standard Indomethacin (IC50 of 5.97 µg/mL). The anticancer activity of Wi38 lung cancer cells showed a significant inhibition ratio of 174.64 ± 0.5 at an IC50 of 62.5 μg/mL, while Caco2 colon cancer cells showed an inhibition ratio of 101.06 ± 0.58 at the same IC5. The extract showed the highest activity against Enterococcus faecalis ATCC 29212 (inhibition zone: 30 ± 0.25 mm). Less activity was observed against Pseudomonas aeruginosa ATCC 90274 (inhibition zone: 16 ± 0.11 mm).